Industrial inorganic chemistry - Benvenuto, Mark A. (De Gruyter graduate., 2015)
All major industrial inorganic chemistry processes, from the largest down to the smaller niche processes that have now become extremely important in maintaining the current quality of life. Importantly, each chapter will include some discussion on the creation of by-products, pollution, and any necessary waste generated in a process, and will discuss ways in which industry has made them more environmentally benign.